RESPONS PONDOK PESANTREN AL-HASANAH TERHADAP MODERNISASI DI KABUPATEN BENGKULU TENGAH - Dewi Penghuni (UIN Fatmawati Sukarno Bengkulu, 2020)
This study aims to find out how the response of Al-Hasanah boarding school to the modernization of information communication technology. The nature of this research is field research (qualitative). The source of this research data is the leadership of boarding school Al-Hasanah, teachers (cleric), board and students of boarding school Al-Hasanah Village Pedati Market District Pondok Kelapa Bengkulu Tegah District. The results showed that modernization at this time can not be sepa- rated from human life and in education until the development of Al-Hasanah boarding school changes. However, as a board- ing school leader, teachers (ustadz), as well as boarders and students of Islamic boarding schools accept modernization, but modernization accepted by boarding schools is not directly swallowed raw, but Al-Hasanah boarding school is very selective in choosing the best and useful for santri for the future. By reason of seeing the fore for students who become alumni after being a santri who plunge society later. the alumni can also enter the general high school after taking education in this pesantren cottage.